The varying effects of benefit types on community members' views of whether they gain from wildlife - Stefan Carpenter (Conservation Science and Practice)
Abstract Community‐based conservation (CBC) is a popular governance approach that asks rural populations to sustainably manage local wildlife resources. CBC programs often rely on the distribution of wildlife benefits to communities to foster tolerance of wildlife, with the idea that those benefits can offset costs arising from human‐wildlife conflict. A survey of residents in four Namibian CBC areas found that different benefit types varied significantly in their relationship with whether respondents felt that wildlife improved their lives. Some higher monetary value benefits evidenced a negative and/or non‐significant relationship with respondents' perceptions, whereas meat‐based benefits were associated with a greater likelihood of residents feeling that they benefited from wildlife. These findings suggest that the impact of different benefit types in CBC programs may depend on a host of cultural/social, psychological, and community‐specific factors. From a practical standpoint, the form of direct monetary benefits may matter, and cultural considerations likely play an important role in determining which and when specific benefits are more effective.